Environmental Factors and their Association with Emergency Department Hand Hygiene Compliance: an Observational Study - Carter, Eileen J. (BMJ Qual Saf, 2015)
OBJECTIVES: Hand hygiene is effective in preventing healthcare-associated infections. Environmental conditions in the emergency department (ED), including crowding and the use of nontraditional patient care areas (i.e. hallways), may pose barriers to hand hygiene compliance. We examined the relationship between these environmental conditions and proper hand hygiene. METHODS: This was a single-site, observational study. From October 2013 to January 2014, trained observers recorded hand hygiene compliance among staff in the ED according to the World Health Organization “My 5 Moments for Hand Hygiene.” Multivariable logisitic regression was used to analyze the relationship between environmental conditions and hand hygiene compliance, while controlling for important covariates (e.g., hand hygiene indication, glove use, shift, etc.). RESULTS: A total of 1,673 hand hygiene opportunities were observed. In multivariable analyses, hand hygiene compliance was significantly lower when the ED was at its highest level of crowding than when the ED was not crowded and lower among hallway care areas than semi-private care areas (OR=0.39, 95% CI 0.28-0.55; OR= 0.73, 95% CI 0.55-0.97). CONCLUSIONS: Unique environmental conditions pose barriers to hand hygiene compliance in the ED setting and should be considered by ED hand hygiene improvement efforts. Further study is needed to evaluate the impact of these environmental conditions on actual rates of infection transmission.